Relationship of smokeless tobacco uses in the perspective of oral cancer: A global burden - Ashek Elahi Noor; Boyapati Ramanarayana (Oral Oncology Reports)
Smokeless tobacco (SLT) use represents a significant and often overlooked public health concern, particularly in regions where cultural practices and societal norms endorse its consumption. Despite misconceptions regarding its safety compared to smoked tobacco, ample evidence suggests that SLT use is strongly associated with the development of oral cancer. This review provides a comprehensive overview of the mechanisms underlying the carcinogenicity of smokeless tobacco and its contribution to the etiology of oral cancer. Firstly, smokeless tobacco products contain a diverse array of carcinogens, including tobacco-specific nitrosamines (TSNAs), polycyclic aromatic hydrocarbons (PAHs), heavy metals, and radioactive elements. These substances exert genotoxic effects, inducing DNA damage, and disrupting cellular homeostasis within the oral mucosa. Furthermore, the direct and prolonged contact between smokeless tobacco and oral tissues facilitates the absorption of carcinogens, exacerbating their local carcinogenic effects. Chronic exposure to smokeless tobacco also induces a state of chronic inflammation and immunosuppression within the oral microenvironment, fostering a permissive milieu for carcinogenesis. The mechanical trauma caused by chewing or holding smokeless tobacco products can lead to the formation of pre-cancerous lesions, providing a fertile ground for malignant transformation over time. Additionally, synergistic interactions between smokeless tobacco use and other risk factors, such as alcohol consumption and human papillomavirus (HPV) infection, further escalate the risk of oral cancer development. Despite the mounting evidence implicating smokeless tobacco in oral cancer etiology, challenges persist in implementing effective preventive measures and promoting tobacco cessation, particularly in regions where SLT use is deeply ingrained in cultural traditions. Therefore, concerted efforts are needed to raise awareness about the health risks associated with smokeless tobacco use, strengthen regulatory policies, and enhance access to evidence-based cessation interventions. By addressing the multifaceted determinants of smokeless tobacco-related oral cancer, we can strive towards reducing the burden of this preventable disease and safeguarding public health on a global scale.